(untitled) (Academia Science Repository, 2023)
In this article, research on moral education, development of methods and forms of Youth Education, analysis of many works written in the educational and moral direction of the educational and educational sphere in historical sources, absorption of their content and essence into young people, at the same time educating the feelings of love of young people for the motherland, teaching them to appreciate